Atlas of Immunology - Cruse, Julius M Lewis, Robert E (CRC Press, 1999)
A pictorial reference, containing more than 1,000 illustrations depicting various concepts of importance in understanding immunology. It demystifies immunology for students, basic scientists, and clinicians. It includes diagrams for various levels of understanding, including basic ideas and a detailed treatments